Pengaruh Kadar High Density Lipoprotein (HDL) dan Usia terhadap Kejadian Peripheral Arterial Disease (PAD) - Daniel Ruslim; Edwin Destra; Joshua Kurniawan; Yohanes Firmansyah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Peripheral arterial disease is a disease that will cause circulatory problem, causing reduction of blood flow inside the artery. This disease approximately has by 6.5 million people above 40 years of age in the United State, and is expected to double with each decade. There are many risk factors for this disease, which includes dyslipidemia and age. High-density lipoprotein (HDL) is one of the lipid component that affects dyslipidemia. This study aims to find out the effects of HDL and age to peripheral arterial disease incidence. The study was done in Yayasan Kalam Kudus, Jakarta on 02 June 2023, with the sample of people aged 18-60 years old, with non-randomized consecutive sampling method. The exclusion criteria on this study are respondents who refused to participate in the study, respondents who are amputated, respondents who has ulcer on the foot, and respondents with ankle-branchial index (ABI) above 1,3. The analysis done in this study are descriptive analysis as in proportion and distribution of centralized data, and analytic analysis using independent T-test and Mann Whitney test as an alternative test, with significance value of 5% (p-value = <0.05). Normality test was done before statistical analysis. From the study, we found out that age is significant role statistically in the incidence of peripheral arterial disease (p-value: 0.028), but levels of HDL are not statistically significant with the incidence of peripheral arterial disease (p-value: 0.084).